The plain language of law. Statement of the problem, general approaches and current trends - Gritsenko, Anna S.; Antonov, Alexey V. (Journal of the Belarusian State University. Law, 2022)
The article is devoted to the problem of drafting laws, contracts and other legal documents in plain language. This has become one of the new trends among scientists and practitioners. The authors, referring to the opinion of experts, indicate that over the past 5–10 years the quality of legal documents in Russia has decreased. This led to an interest in what the wording of the law should be in order for it to be clear and understandable. The article analyses foreign experience, as well as new trends, including the use of artificial intelligence and methods of deep neural networks in rule-making.
Keywords: plain language; law; preparation of regulations; requirement for clarity and simplicity; rule-making; machine-readable law